Privacy protection scheme for internet of vehicles based on homomorphic encryption and block chain technology - Ruijin WANG; Yucheng TANG; Weiqi ZHANG; Fengli ZHANG (网络与信息安全学报)
In order to solve the problem that the security of traditional internet of vehicles devices is relatively low,which may threaten the privacy of users,a privacy protection scheme based on homomorphic encryption and block chain technology was proposed.This scheme added the authentication service composed of two level nodes to the proposed model to realize the permission control of roles in the model.In order to record the information of the internet of vehicles devices,a new block data structure based on homomorphic encryption (HEBDS) was proposed,which enabled the privacy data to be written into the block after being processed by the Paillier encryption algorithm,and then written into the blockchain network by the gateway node obtaining the accounting right.This scheme realized the data processing in ciphertext state,and made up for the shortage of all data disclosure in blockchain network.Through the analysis of the security of the scheme,it is proved that the scheme has the characteristics of unforgeability and privacy data security.Through homomorphic encryption of privacy data and upload to blockchain network,the scheme can distribute,share and calculate privacy data in ciphertext state,which can protect customer privacy more effectively than traditional internet of vehicles model.